Is differential diagnosis attainable in disarticulated pathological bone remains? A case-study from a late 19th/early 20th century necropolis from Juncal (Porto de Mós, Portugal) - Assis, Sandra (2018)
Differential diagnosis is a fundamental step in every palaeopathological study. It is a challenging exercise since many intrinsic and extrinsic factors may negatively impact the accurate interpretation of bone changes in human skeletal remains. Among these, the completeness and preservation of skeletal elements plays a significant role. This study aims to explore the limits of differential diagnosis in the analysis of disarticulated, fragmented bones. The sample consists of eleven adult long-bone fragments with noticeable changes. The remains were identified in a dis-articulated skeletal assemblage from the former necropolis of Juncal (Porto de Mós, Portugal), which probably closed in the late 19th century/early 20th century. They were analysed visually and with X-radiography, and the changes carefully described prior to differential diagnosis. Five bones presented signs of healed bone trauma and one showed features compatible with leg amputation. Periosteal reactions were observed in several bones, one of them resembling changes consistent with an overlying skin ulcer. Two bone specimens were identified as belonging to the same individual due to the matching bone changes. Despite the incomplete remains, a broader diagnosis was possible for most cases, which facilitated a discussion of health, medical and social care among the inhabitants of the region.